Impact of sickle cell anaemia on cardiac chamber size in the paediatric population. (14th November 2016) - Adjagba, Philippe M.; Habib, Gaston; Robitaille, Nancy; Pastore, Yves; Raboisson, Marie-Josée; Curnier, Daniel; Dahdah, Nagib
Abstract: Purpose: Sickle cell disease is known to cause various degrees of vasculopathy, including impact on heart function. The aims of this single-centre, retrospective study were to assess cardiac chamber size and function and the relationship with haematological indices such as haemoglobin, aspartate aminotransferase, reticulocytosis and bilirubin, lactate dehydrogenase in sickle cell disease. Methods: Right ventricle and left ventricle diastolic diameters, left ventricle mass estimate, left ventricle shortening fraction, myocardial performance index, and an index of myocardial relaxation (E/E') were calculated and correlated with haematological parameters. Results: A total of 110 patients (65% haemoglobin SS, 29% haemoglobin SC) were studied at a mean age of 12.14±5.26 years. Right ventricle dilatation and left ventricle dilatation were present in 61.5 and 42.9%, respectively. Left ventricle mass was abnormal in 21.9%; all patients had normal myocardial performance index, 31.4% had abnormal E/E', and left ventricle shortening fraction was low in 38.1%. Cardiac dilatation was best correlated with haemoglobin, aspartate aminotransferase, reticulocytosis and bilirubin. Best subset regression analysis yielded significant additional prediction for right ventricle or left ventricle dilatation with haemoglobin, bilirubin, and lactate dehydrogenase. Abnormal E/E' was solely predictable with haemoglobin level. Hydroxyurea-treated patients had improved diastolic function. Conclusion: Right ventricle dilatation was more prevalent than left ventricle dilatation. The long-term consequences of right ventricular dilatation, clinical consequences, and association with pulmonary vasculopathy need to be further determined.